2002
DOI: 10.1042/0264-6021:3610097
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the influence of the high-mobility group box 1 protein on DNA binding and transcriptional activation by the androgen, glucocorticoid, progesterone and mineralocorticoid receptors

Abstract: We performed a comparative analysis of the effect of high-mobility group box protein 1 (HMGB1) on DNA binding by the DNA-binding domains (DBDs) of the androgen, glucocorticoid, progesterone and mineralocorticoid receptors. The affinity of the DBDs of the different receptors for the tyrosine aminotransferase glucocorticoid response element, a classical high-affinity binding element, was augmented up to 7-fold by HMGB1. We found no major differences in the effects of HMGB1 on DNA binding between the different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…Nevertheless, it is interesting to notice that the presence of NPM did not affect the mobility of the complexes and that the use of an anti-NPM antibody did not result in the supershift of the retarded protein-DNA complex as would have been expected if NPM was present in the complex. Similar findings have already been reported for the highmobility group box 1 (HMGB1) protein which facilitates the DNA binding of several steroid receptors, including AR, without being present in the DNA/ receptor complex in EMSA experiments (Boonyaratanakornkit et al, 1998;Verrijdt et al, 2002). In a general hit-and-run mechanism, the authors have suggested that the HMGB1 protein might be a transient and unstable component of the steroid receptor/steroid response element complex that does not take part in the interactions within the final transcription activation complex.…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, it is interesting to notice that the presence of NPM did not affect the mobility of the complexes and that the use of an anti-NPM antibody did not result in the supershift of the retarded protein-DNA complex as would have been expected if NPM was present in the complex. Similar findings have already been reported for the highmobility group box 1 (HMGB1) protein which facilitates the DNA binding of several steroid receptors, including AR, without being present in the DNA/ receptor complex in EMSA experiments (Boonyaratanakornkit et al, 1998;Verrijdt et al, 2002). In a general hit-and-run mechanism, the authors have suggested that the HMGB1 protein might be a transient and unstable component of the steroid receptor/steroid response element complex that does not take part in the interactions within the final transcription activation complex.…”
Section: Discussionsupporting
confidence: 70%
“…Among the short list of this type AR cofactors are HMG1/2 and nucleophosmin. HMG1/2 enhances DNA-binding activity of steroid hormone receptors such as progesterone receptor, glucocorticoid receptor, and AR (51,52). Nucleophosmin was shown to enhance AR DNA-binding and transcriptional activity (53).…”
Section: Discussionmentioning
confidence: 99%
“…10 and references therein). The reporter construct driven by the E1b promotor and containing two copies of the rat tyrosine aminotransferase-GRE was described previously (47). The thymidine kinase minimal promotor-driven reporter construct containing the slp and sc upstream enhancers and the C3 (1) intronic fragment as well as the pb promotor-driven construct have also been described (10).…”
Section: Methodsmentioning
confidence: 99%